(untitled) (Modern education and development, 2025)
The article states that Artificial Intelligence technologies are currently bringing positive changes to various aspects of society, including production, education, healthcare, finance and public safety, and that economically, artificial intelligence is creating opportunities for automating production, creating innovative products and creating new jobs. The impact of artificial intelligence on the economic and social system, its advantages and problems are considered.